The Influence of Promotional Policies on Consumer Loyalty in Auto 2000 Sisingamangaraja Medan - Henri Saragih (International Journal of Asian Business and Management, 2024)
The purpose of this research is to determine and analyze the influence of promotional policies on consumer loyalty at Auto2000 Sisingamangaraja Medan. The variables used in this research are advertising (X1), sales promotions (X2), personal sales (X3) consumer loyalty (Y). The population used in this research was Auto 2000 Sisingamangaraja Medan consumers as of July 2019 to September 2019, totaling 1800 people. Using the Slovin formula, the sample size was 95 people. The data analysis used in this research is multiple linear regression analysis. The results of the multiple linear regression equation obtained from the research results are Y = 6.265+ 0.471 X1 + 0.178 X2 + 0.391 X3 + e. The results of the research are that advertising and personal sales variables partially have an influence and significance on service quality. Simultaneously, advertising, promotion and personal sales have a more positive and significant effect on consumer loyalty with a value of R2 = 57.2%, which means that the advertising, promotion and personal sales variables have an effect on consumer loyalty by 57.2%. It is recommended to future researchers that the results of this research can become a reference that can provide additional knowledge and comparisons in conducting research in the future